2004
DOI: 10.1191/1352458504ms1010oa
|View full text |Cite
|
Sign up to set email alerts
|

No major association of A poE genotype with disease characteristics and MRI findings in multiple sclerosis

Abstract: In this cohort no association of the ApoE genotype with disease susceptibility nor clinical and MRI measures could be identified. However, combined analysis of published data could not definitely exclude the possibility of a minor role for epsilon2-carriership in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
1
21
0
5
Order By: Relevance
“…12,15,16,18,20,22,23,25,28 Furthermore, with regard to Apo o, genetic variation was not found to be of significant importance to the age of onset, which is in agreement with previous findings. 10,15,16,18,22,23,32 The present study supports the hypothesis that the Apo o4 allele is associated with a faster disease progression in MS. A significant association was found in two subgroups, specifically in patients with disease duration of 10 years or less and in patients with RRMS. Previous studies examining the association between Apo o4 and disease progression have demonstrated contradictory results, although most studies showed an association.…”
Section: Discussionsupporting
confidence: 91%
“…12,15,16,18,20,22,23,25,28 Furthermore, with regard to Apo o, genetic variation was not found to be of significant importance to the age of onset, which is in agreement with previous findings. 10,15,16,18,22,23,32 The present study supports the hypothesis that the Apo o4 allele is associated with a faster disease progression in MS. A significant association was found in two subgroups, specifically in patients with disease duration of 10 years or less and in patients with RRMS. Previous studies examining the association between Apo o4 and disease progression have demonstrated contradictory results, although most studies showed an association.…”
Section: Discussionsupporting
confidence: 91%
“…The frequencies in the general population have been reported to be 10%, 74%, and 16% for ε2, ε3, and ε4, respectively (31). Owing to the fact that the E3 isoform was the most common form in various studies investigating the relationship between the general population and APOE, as well as between MS and APOE, E2 and E4 are considered variants (28,30,32,33,34,35,36,37,38,39,40,41,42,43). The prevalence of MS in Turkey is between that of the European countries in which MS is common and the Asian countries in which MS is less common.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, we interpreted this finding as evidence for more aggressive disease, greater vulnerability to injury or impaired repair. It was also evident that differences between apoE genotypes were more marked with regard to morphologic than to [18] 2003 72 L Lower and more rapidly decreasing NAA with apoE q4 allele Enzinger C [17] 2004 99 L ApoE q4 associated with accelerated brain tissue loss and higher proportion of lesions developing into ''black holes'' Zakrzewska-Pniewska B [36] 2004 114 CS No association with lesion load and brain volume De Stefano N [40] 2004 76 CS ApoE q4 associated with lower brain volume Zwemmer JN [11] 2004 871 L No association with lesion load and brain volume CS = cross-sectional. L= longitudinal.…”
Section: Multiple Sclerosis and Apoementioning
confidence: 97%
“…These investigations commonly agree that the apoE genotype is not a risk factor for MS although some trend towards a higher frequency of the apoE q2 allele in MS patients than controls cannot be completely excluded [11]. There is also no good evidence for an association of the apoE polymorphism with a specific course of MS, i.e.…”
Section: Multiple Sclerosis and Apoementioning
confidence: 97%